MAPPING OF THE CONJUNCTIONS APPLICATION IN A COLLECTION OF STORIETTE “ALONG THE AQUATOR” BY RETNO NIKO USULI - Sadri Sadri; Gazali Lembah; Ida Nur’aeni (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
Mapping of the Conjunctions Application in A Collection of Storiette “Along the Equator” By Retno Niko Usuli. Background in this research is: (1) How the mapping of the conjunctions application in a collection of storiette: Along the Equator by Retno Niko Suli. Data collecting method and technoque is extralingual matching method. The mothod used in the stage of prsenting the result of data analysis in this research is the informal method. The result of this study are as follows: based on th type of coordinating conjunctions are divided into 5 types, namely coordinates, subordinates, correlation, inter-sentence, and intra sentences. Subordinate conjunctionns were the most commonly found counjunctions, with 316 findings and coordinate conjunctions with 118 findings. Subordinate conjunctions are multilevel sentences that are widely used in short story writing as well as coordinating conjunctions which are equivalent compound sentences. The fewest occurrences of conjunctions found were correlation and intra-sentence conjunctions. In writing this storiette, the writer rarely uses correlation and inter-sentence conjunctions. In this storiette there are no conjunctions between paragraphs. This research only discusses the mapping of 5 types of conjunctions. Therefore, for other researchers who want to examine mistakes in the use of conjunctions, it will be more interesting. For other researchers, this research can be used as a reference for further research materials and can further deepen or expand the study of discourse.